Cultural value of water and western water management: an Australian Indigenous perspective. Issue 1 (2nd January 2021) - Moggridge, Bradley J.; Thompson, Ross M.
ABSTRACT: Water is a critical issue for governments and community in an Australian context, and internationally. First Peoples of Australia, its Indigenous peoples, have over 65, 000 years of connection and understanding of water, held by more than 250 distinct Indigenous Nations that occur from the wet tropics, through desert country and south to the temperate zone, river lands and alpine regions. The value of water is central to Indigenous peoples' being and culture, but since European colonisation in 1788, water has been subject to pumping, storage, diversion, extraction and pollution and without Indigenous people's council. Most recently, water has been attributed a market value to sell and trade on a market that moves up and down with availability (drought, flood or in-between). Indigenous peoples have very small water entitlements despite the high value they place on water and the strong connection water has to their sense of identity, spirituality and culture. There is both a need and a great opportunity for Indigenous people to uphold and protect their water values through Indigenous-grounded methodologies or Indigenous-led water research, and so as to integrate Indigenous water knowledge into science and policy.